2000
DOI: 10.1002/clc.4960230410
|View full text |Cite
|
Sign up to set email alerts
|

Potential reduction of costs and hospital emergency department visits resulting from prehospital transtelephonic triage—the shahal experience in israel

Abstract: SummaryBackground: The rising cost of services provided by hospital emergency departments is of major concern. Attempts to reduce the costs of emergency cardiac care have thus far focused primarily on medical and administrative management in the hospital. The role of the patient in appropriate prehospital decision-making has been generally ignored.Hypothesis: Membership in "Shahal" (an integrative telemedicine system) may have beneficial effects on patient decision-making and national health costs.Methods: Dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1
5

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 7 publications
1
13
1
5
Order By: Relevance
“…These findings correspond to the data described in national and international literature indicating that telemonitoring has a significantly positive effect in the realm of acute ischaemic attacks reducing cardial mortality and in-hospital-stays as well as admissions Arntz & Schultheiss 2002;Roth et al 1997;Roth et al 2000;Roth et al 2001). …”
Section: Telemonitoring Of Chronic Heart Insufficiencysupporting
confidence: 90%
See 1 more Smart Citation
“…These findings correspond to the data described in national and international literature indicating that telemonitoring has a significantly positive effect in the realm of acute ischaemic attacks reducing cardial mortality and in-hospital-stays as well as admissions Arntz & Schultheiss 2002;Roth et al 1997;Roth et al 2000;Roth et al 2001). …”
Section: Telemonitoring Of Chronic Heart Insufficiencysupporting
confidence: 90%
“…On the other hand, there are estimations to be found that insist that more than 50% of cases of inpatient care could be avoided, if the patient was better informed direct access for accident ambulance to intensive care units, competence insecurity in the emergency room, lack of clear guidelines of how to proceed in case of coronary syndromes or if administrative procedures cause further delay (Arntz et al 2000). Furthermore, misjudgement and repression of patients also play an essential role -the doctors' major objective is thus to thoroughly inform the patients at risk and their relatives (Roth et al 2001).…”
Section: Telemonitoring Of Chronic Heart Insufficiencymentioning
confidence: 99%
“…A more frequent execution of tests in primary care facilities was expected and does meet the main goals of the tool, to bring the primary care closer to the secondary or tertiary care, thus reducing bottlenecks in the system and facilitating the urgent care of severely ill patients [6][7][8][9]17 . When the possibility of cardiovascular abnormality detected by the ECG report is evaluated, most tests showed some abnormality.…”
Section: Discussionmentioning
confidence: 99%
“…This growth has been even greater in Asynchronous Telemedicine, in which the tests are sent to a server for further analysis and reporting by a specialist. It is considered a low-cost timesaving technology with a potential to save lives 6 , thus decreasing the distance between the primary care and secondary care 7 .…”
Section: Introductionmentioning
confidence: 99%
“…A cost per quality-adjusted life year gain of €1927 was calculated in a regional registry for pre-hospital electrocardiogram diagnosis of ST-elevation acute myocardial infarction [60]. Similarly, an 83$ individual cost saving per year was figured in another emergency setting using telemedicine support [61].…”
Section: Telemedicine: Considerations On Cost-efficacymentioning
confidence: 99%